Perspectives of transformative learning and professional agency: A native Chinese language teacher’s story of teacher identity transformation in Australia - Yang, Suling; Han, Jinghe (Frontiers in Psychology, 2022)
The notion of teacher identity has gained momentum in second language (L2) teacher education in the past decade. However, the research into Chinese as a Foreign Language (CFL) teacher identity has yet to receive more attention. The study employed a narrative inquiry to explore a native Chinese CFL in-service teacher’s identity negotiation and transformation within an international teacher education program. Self-reported narrative accounts, including multiple in-depth interviews and once-a-term reflective journals, were complemented by field notes and program documents. This data captured how the participant teacher negotiated internally with self and externally with the new environment to pursue professional growth. Mezirow’s (2000) transformative learning theory was used to reveal the cognitive trajectory of the participant’s teacher identity transformation with critical reflection as the central stage. Further, guided by the framework of professional agency (Eteläpelto et al., 2013), the study also unraveled multiple external and internal influences on the transformational trajectory. The findings confirmed the value of integrating these two theoretical perspectives to explore language teacher identity development and offer insights into L2 teacher education practices focusing on teacher identity development.